Familiar story structures possess an evolutionary edge in memory - Abla Alaoui-Soce; Diana I. Tamir (PLoS ONE, 2026)
Human beings demonstrate a universal impulse to share and consume stories. Over generations of transmission, within and across cultures, stories have evolved to develop regularities in their internal structures. Here, we investigated how two features of story structure – coherence and familiarity – impact recall as participants retold a story 5 days in a row. We predicted that familiar and coherent structures would be more stable over retellings. We measured stability using two novel story similarity measures of the (1) degree of structural change within storytellers, and (2) similarity in remembered structure across storytellers. Study 1 first validated our story similarity measure. Studies 2 and 3 then tracked the evolution of stories that varied in coherence and familiarity, respectively, using novel stories adapted from the popular “Cinderella” structure. Results showed that all stories became more structurally stable across retellings, with stories moving in a consistent direction ( i.e. , towards a consistent final form). However, retellings of a story with a more coherent and familiar structure showed both greater stability within and similarity across minds than retellings of a story with an incoherent (Study 2) or unfamiliar structure (Study 3). Thus, using novel tools to measure story evolution, our findings suggest that familiarity and coherence of a story structure offered it an advantage in memory, both within and across minds.